Answer:
Here we have:
g(x) = 2*√x
And we know that it is related to a parent function, where the parent functions are:
Linear Function: f(x)=x.
Quadratic Function: ݂f(x)=x^2.
Square Root function: f(x)= √x.
Absolute Value function: f(x)=|x|
Cubic function: f(x)=x^3.
Cube Root function: f(x) = ∛x
Logarithmic function: f(x)=log x or f(x)=In x.
Exponential function: f(x) = a^x.
a) Because g(x) = 2*√x
We can see that it is related to the square root function, then the parent function is:
f(x) = √x
b) now we want to write g(x) in terms of f(x)
we have:
g(x) = 2*√x
we can replace √x by f(x)
then we get:
g(x) = 2*f(x)
Now we have g(x) in terms of f(x)